Efetividade da formação a distância para gestores da educação básica: a experiência da Escola de Gestores na UFMG - Jacqueline de Castro Laranjo (2016)
This thesis presents the results of an evaluation of the effectiveness of distance learning. Our research focused on the Specialization in School Administration course of the National School for Basic Educational Administrators Program, developed by the Ministry of Education, and offered by the Federal University of Minas Gerais, between 2008 and 2011, with the intention of identifying its effects in both the personal and professional spheres of the graduates. As our hypothesis, we sought to establish the difference in management as performed by the graduates of the course, after their lato sensu distance learning in school management. We utilized Kirkpatrick's four levels of training model (1976) with Hamblin'smodifications (1978). This model was chosen because our analysis was focused on the learners and not on the means and tools of the course. We performed a case study and opted for a qualitative-quantitative methodology within the limits of its specific features, so that their interpretation would be complementary and describe the facts and the realities observed. We used four sources of evidence: questionnaires, analysis of the documents, interviews andobservation. The justification for this study was the need to expand, strengthen and consolidate the amount of both latu sensu and stricto senso post-graduate programs that are focused on the training of basic education professionals nationally, as was pointed out in the final document of the National Education Conference in 2010. The results showed the difference between school administration performed prior to and following the graduates' participation in the course, and furthermore, showed that this was not a chance difference. The data showed a direct relationship between the content covered in the course and the learningdemonstrated by those who completed it. We identified the use, by the graduates, of several tools with the intention of consolidating democratic attitudes and abilities in relation to school administration. While only 13% (12/85) of pedagogical political projects were developed collectively by the school community prior to the course, 81% (73/85) were developedcollectively afterwards. We also observed a significant increase (P-value <0.05) in the percentage of cooperative outside support agents for administration in the schools of the graduates. There was also a change in the behavior of the graduates in relation to their more frequent participation in the school's pedagogical area, whereas prior to the course this involvement was more commonly seen in the administrative area. The qualitative analysis points to a dissonance in relation to the final result, the implementation of democratic school administration in schools was not the same for all of the graduates who were interviewed, the results are closely related to the school's external environment. Still, we believe that these results do not disqualify the effectiveness of the training. We therefore conclude that there is consensus in the data demonstrating the effectiveness of the training in school management,due to the fact that change does not occur in the same way nor at the same time for everyone, so upon analysis the course is shown to be strategic for the inclusion of cooperative practices in schools within in a more transformational approach: democratic school administration.